2011
DOI: 10.1007/s00402-011-1368-4
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Total Evolutive Shoulder System (TESS®): a single-centre study of 56 consecutive patients

Abstract: TESS prosthesis showed promising short-term results with few complications. The reverse version could be implanted without stem if initial stability was adequate. Long-term follow-up is required to confirm the results of this innovative system in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…The humeral implant stability was of concern initially. With the numbers given and considering eventual limitations related to the volume of this study, we found encouraging results with adequate humeral fixation in both anatomical and reverse versions [1,13,14]. In our study, with a mean follow-up of 39 months (15-66 months), there were no signs of humeral loosening after stemless implantation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The humeral implant stability was of concern initially. With the numbers given and considering eventual limitations related to the volume of this study, we found encouraging results with adequate humeral fixation in both anatomical and reverse versions [1,13,14]. In our study, with a mean follow-up of 39 months (15-66 months), there were no signs of humeral loosening after stemless implantation.…”
Section: Discussionmentioning
confidence: 48%
“…Grammont and Baulot revolutionised the treatment of cuff tear arthropathy (CTA) in the 1980s by introducing the concept of reverse shoulder arthroplasty (RSA), which moved the centre of rotation medially and distally [1]. Besides CTA, the indications for RSA include comminuted shoulder fractures, revisions, rheumatoid arthritis (RA) and severe osteoarthritis (OA) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors achieved an anatomical reconstruction in all patients, even in post-traumatic arthritis cases in which no tuberosity osteotomy was required. In 2011, Kadum et al (15) reported on a group of 56 patients treated for a variety of shoulder conditions, including OA, post-traumatic arthritis, rotator cuff arthropathy, and proximal humeral fracture. This group was implanted with the Biomet TESS by standard hemiarthroplasty, primary total shoulder arthroplasty, or reverse arthroplasty, either with or without the optional intramedullary stem attachment to the corolla.…”
Section: Results: Literature Reviewmentioning
confidence: 99%
“…The mean Constant score in this cohort was 75. Kadum et al followed a heterogeneous group cohort of 56 patients but unfortunately only had 14-month follow-up on average and as short at 9-month follow-up in some cases [25]. This cohort included 22 patients with an anatomic nonstemmed component.…”
Section: Biometmentioning
confidence: 99%